Finite element modeling of traumatic brain injury: Areas of future interest. (December 2022) - Griffiths, Emma; Budday, Silvia
Abstract: The use of the finite element (FE) method to simulate traumatic brain injury (TBI) has been an area under development and research for many years. The aim is to accurately reproduce and evaluate the resulting brain damage that would otherwise be inaccessible. Computational simulations can assist the diagnosis of injuries and early detection of long-term damage in order to advance preventative measures and implement early treatments. Here, we discuss a few new and emerging trends of FE models for TBI. We highlight advancements in two main areas: FE head models and brain tissue material models. We discuss how FE models can be improved to have greater anatomical and mechanical biofidelity, resulting in more accurate TBI simulations. Our aim is to stimulate future research activities in important areas that have so far been underexplored and can significantly accelerate the relevance of TBI FE models for clinical use in the future.